2019
DOI: 10.1038/s41598-019-42525-y
|View full text |Cite
|
Sign up to set email alerts
|

Brevibacterium from Austrian hard cheese harbor a putative histamine catabolism pathway and a plasmid for adaptation to the cheese environment

Abstract: The genus Brevibacterium harbors many members important for cheese ripening. We performed real-time quantitative PCR (qPCR) to determine the abundance of Brevibacterium on rinds of Vorarlberger Bergkäse, an Austrian artisanal washed-rind hard cheese, over 160 days of ripening. Our results show that Brevibacterium are abundant on Vorarlberger Bergkäse rinds throughout the ripening time. To elucidate the impact of Brevibacterium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 87 publications
(124 reference statements)
0
23
0
Order By: Relevance
“…The presence of plasmids in Brevibacterium is rare with only a few described in the literature (Sandoval et al, 1985; Kato et al, 1989; Ankri et al, 1996; Moore et al, 2003; Nardi et al, 2005; Anast et al, 2019). We searched for the presence of plasmids and only one strain, B. linens ATCC 19391, harbored one.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of plasmids in Brevibacterium is rare with only a few described in the literature (Sandoval et al, 1985; Kato et al, 1989; Ankri et al, 1996; Moore et al, 2003; Nardi et al, 2005; Anast et al, 2019). We searched for the presence of plasmids and only one strain, B. linens ATCC 19391, harbored one.…”
Section: Resultsmentioning
confidence: 99%
“…Psychrobacter L7 (Gammaproteobacteria) most likely belongs to the species Psychrobacter celer, and Brevibacterium S111 (Actinobacteria) may represent a novel, yet undescribed, Brevibacterium species. Psychrobacter L7 and Brevibacterium S111 were isolated from the rinds of Vorarlberger Bergkäse, an Austrian mountain cheese produced in western Austria [34,35]. Quantitative PCR and whole genome analysis revealed that Psychrobacter L7 and Brevibacterium S111 are highly abundant on cheese rinds throughout ripening and may significantly contribute to the cheese ripening process [34,35].…”
Section: Strains and Culture Conditionsmentioning
confidence: 99%
“…The microbial system of washed rind cheeses is also very complex, and its balance is a key to develop the specific cheese flavour and colour. Brevibacterium aurantiacum is among the most important bacterial species used as a surface ripening culture for such cheeses (Cogan et al ., 2014; Bonham et al ., 2017; Pham et al ., 2017; Anast et al ., 2019; Levesque et al ., 2019). This bacterial species is part of the taxonomic group of orange pigment‐producing Brevibacterium genus (Gavrish et al ., 2004), in which Brevibacterium linens is the type species (Gavrish et al ., 2004; Forquin et al ., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…During cheese maturation, the ripening cultures are added to the curds in successive surface washes, contributing to the final organoleptic characteristics (Rattray and Fox, 1999; Onraedt et al ., 2005; Motta and Brandelli, 2008). Even though these bacteria have been receiving growing interest lately (Bonham et al ., 2017; Pham et al ., 2017; Anast et al ., 2019), B. aurantiacum phages have yet to be isolated and characterized. Although complex, cheese rind microbial communities have been shown to be a tractable system that can be used to understand the dynamics influencing microbial assembly, succession and function (Wolfe et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%